Tracking Sodium Cluster Dynamics in Hard Carbon with a Low Specific Surface Area for Sodium-Ion Batteries - Yauhen Aniskevich; Yu, Jun Ho; Kim, Ji Young; Shinichi Komaba; Seung-Taek Myung (Wiley-VCH Verlag, 2024)
Here, the sodium storage mechanism in commercial grade hard carbon with a low surface area is comprehensively investigated using electrochemical impedance spectroscopy (EIS), the galvanostatic intermittent titration technique, and in situ Raman spectroscopy for fresh and cycled electrodes. The reversible shift of the carbon G-band peak on Raman spectra and substantial change of the charge-transfer resistance in the sloping region of the voltage profile indicates the intercalation of sodium ions into hard carbon, whereas the low-voltage plateau is associated with the pore-filling process. In situ Raman analysis at low frequencies reveals that the pore filling is progressed via formation of small sodium clusters in closed pores. Prolonged cycling demonstrates that intercalation is stable and consistent throughout multiple charge？discharge cycles. The transition from intercalation to pore filling strongly affects the diffusion behavior, leading to considerably slower diffusivity at low voltage. The EIS effectively differentiates the contribution of adsorption to charge storage. The gradual growth of the solid-electrolyte interphase layer affects the rise of the interfacial resistance as cycling progresses. In combination with the slower diffusivity, the low-voltage plateau region strictly impedes fast de/sodiation and eventually causes capacity fade.